Competencias transversales: percepción del alumnado de la Universidad Católica Argentina (Investigaciones) - Corbella, María Valeria (2024)
Transversal competencies are those skills necessary for employment integration and the reduction of the existing gap between university education and employability. However, higher education does not always include them in training programs, as the focus continues to be on content acquisition. Therefore, this study investigated the development of transversal competencies from the perspective of final-year undergraduate students at Catholic University of Argentina. Its design is mixed, exploratory in nature, and involved a sample of 226 participants. A specifically designed questionnaire was used, and the data were analyzed using SPSS and Atlas.ti. The results indicate that most participants perceive a good development of transversal competencies but that these are primarily acquired in contexts outside the university. They suggest that the application of theoretical content to practice should be strengthened to align education with the job market, along with the implementation of active pedagogical methodologies, faculty training, and curriculum updates. These findings are crucial for understanding the current situation of university education in transversal competencies and confirm the need to reconsider university curricula and teacher training in innovative pedagogies.